Rare case report of accidental intravenous injection of oral probiotic - Mehta, Madhuri; Gupta, Vani K.; M. U. Rahman, Mohammad Faiz (International Journal of Research in Medical Sciences, 2023)
Oral probiotics containing spores of Bacillus clausii are given to the patients who have undergone major surgery or are on long term antibiotic course, to restore intestinal microbial flora. We are reporting a rare case where the oral probiotic suspension was injected intravenously by mistake. We shall be discussing in detail the reactionary changes caused by erroneous injection of oral probiotics in the body, its effects, complications and treatment of the reactionary changes.